A Comprative Analysis of Gen Z Regarding Preferences Delivery Time Taken Byblinkit and Big Basket an Ahemdabad City - Nirav, Makwana; Vidani, Jignesh; Anjali, Zala (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the relationship between age and various factors that influence consumer behavior in grocery delivery services, specifically focusing on Blinkit and Big Basket. Through a series of Chi-square tests, the study tests hypotheses related to preference for delivery apps, perceived speed of delivery, satisfaction with service, and willingness to pay for expedited delivery. This study highlights the importance of adopting a more holistic approach to understanding consumer behavior in grocery delivery, emphasizing the role of technology and operational efficiency. By addressing universal consumer motivations, businesses can increase customer satisfaction and loyalty in a competitive market. Future research is recommended to explore other demographic and psychographic factors, as well as the impact of new technologies and sustainability concerns on consumer preferences